Identification of the factors affecting consumer behavior in the selection of sustainable packaging - Haddadian, Sanam. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
Packaging features of the products are crucial elements in consumer purchasing decisions. The need for sustainable packaging and the awareness of the consumers are growing each day. However, consumers' environmental attitudes and behavior may occasionally be disturbed by various factors. The aim of this study is to "Identify the Factors Affecting Consumer Behavior in the Selection of Sustainable Packaging." Since the factors influencing consumer behavior in choosing sustainable packaging must first be revealed in order to finally design a model for it, a mixed research approach must be used. For this purpose, the exploratory method of mixed research method has been used. In this research, first, the qualitative method is used to identify the main components, and then the quantitative method is applied in order to test the final model or answer the research questions. In the qualitative section, library or documentary methods were used to collect information. In the quantitative part, a survey method and a questionnaire were used to collect information. The questionnaire was designed based on the identified open codes. In this study, we propose a comprehensive model for consumer behavior in choosing sustainable packaging and review the validity of the proposed model using a qualitative model.
Keywords: Package goods industry.; Packaging -- Environmental aspects.; Packaging -- Technological innovations.